Antecedents of managers' pro-environmental intentions and behaviour - Saira Kharuddin
Environmental issues, such as air and water pollution, resources scarcity, and global warming, are becoming major concern. These environmental problems have often been created by businesses and industries. This has led many countries to develop environmental regulations that aim to control organisations' activities to improve environmental protection outcomes. Such concerns raise the need for organisations to display more effective environmental management conduct. Past studies have largely emphasised organisations' environmental practices, but very limited studies have focused on managers' behaviour in enhancing the effectiveness of their business environmental practices. The purpose of this research is to further understand the antecedents that influence managers' pro-environmental intention. In addition, this study also hopes to provide a better understanding of the mediation effect of their intentions towards their pro-environmental behaviour. Therefore, Theory of Planned Behaviour was utilised to examine and determine which antecedents are the most influential for managers to be environmentally and financially responsible in preserving the environment. This study extends the TPB model by the inclusion of religiosity as a predictor to further explain managers' intentions and behaviours. Questionnaires were sent to managers in environmentally sensitive companies listed on Bursa Malaysia. The data collected from a sample of 99 managers were analysed using partial least squares structural equation modelling. The results provide support that managers' subjective norms and religiosity values were significant predictors of intention for managers to conduct organisations' environmental practices. However, managers' personal environmental attitudes and their belief about the importance of fulfilling organisations' economic objectives were acknowledged as having low impact on their intention to perform pro-environmental practices. With regard to managers' environmentally responsible behaviour, it is noted that significant improvement can be developed in building managers' environmentally responsible behaviour by focusing on subjective norms requirements and managers' religious values. This study, however, also provides evidence that though managers have high intention to preserve the environment, it is not enough for them to be financially responsible in exercising such actions. Post survey interviews were conducted to further assist in understanding the factors that might be feasible or useful for managers to protect the environment and explain the challenges encountered by them to be financially responsible. Theoretically, TPB provides some insights into the important attributes required by managers to be environmentally and financially responsible in preserving the environment. It addresses the recent call in the literature to research the antecedents that influence managers' intention to execute organisations' environmental practices that further lead them to perform pro-environmental behaviour. Hence understanding managers' behaviour within their workplace could assist organisations in creating a motivated environment for managers to effectively perform their expected intentions and behaviour. There are several limitations of this study, such as the data only focused on environmentally sensitive industries and there are probably other important factors that have not been examined in this study that might influence managers' behaviour.